Making sense of self-esteem - Leary, Mark R. (1999)
Sociometer theory proposes that the self-esteem system evolved as a monitor of social acceptance, and that the so-called self-esteem motive functions not to maintain self-esteem per se but rather to avoid social devaluation and rejection. Cues indicating that the individual is not adequately valued and accepted by other people lower self-esteem and motivate behaviors that enhance relational evaluation. Empirical evidence regarding the self-esteem motive, the antecedents of self-esteem, the relation between low self-esteem and psychological problems, and the consequences of enhancing self-esteem is consistent with the theory.